Faktor yang mempengaruhi Minat Belajar Siswa pada Mata Pelajaran Biologi Kelas Xl MIPA SMA Negeri 4 Pekanbaru Tahun Ajaran 2022/2023 - Desi Lestari; Mellisa (Perspektif Pendidikan dan Keguruan, 2023)
This study aims to determine the factors of student interest in biology in SMA Negeri 4 Pekanbaru in the 2022/2023 academic year. This research was conducted in March - November 2022. This research is a quantitative descriptive study. The method used in this study is a survey method. The instruments used in data collection were observation, questionnaires, interviews and documentation. The number of samples in this study were 100 students. The questionnaire distributed consisted of 31 statements. Based on the results of the study, the factors that influence students' interest in learning are being interested in teachers and being tenacious in learning. Factors interested in teachers are in the good category with a percentage of 79.5%. And the second factor is tenacity in learning is in the good category with a percentage of 79.5%. From the results of the study, it can be concluded that students' learning interest in the material of the human circulatory system in biology subjects at SMA Negeri 4 Pekanbaru in the 2022/2023 academic year is in the good category with a percentage of 76.22%.